PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN (Studi Empiris Pada Perusahaan-Perusahan Keuangan Yang Terdaftar Dalam CGPI Tahun 2006 Sampai 2010) - Edi Purnomo; Erwin Saraswati (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
This research has purpose to analize the influence of Good Corporate Governance (GCG) implementation is proxied by profitability, leverage, liquidity, activity, and Good corporate governance against bankruptcy analysis (z score). Population in this research is financial company sector listed in Corporate Governance Perception Index (CGPI). The sampling technique using purposive sampling, and the number of sample as many as 31 companies. Analysis methods in this research is the method of multiple regression analysis. Results of this research indicate there was influence of corporate governance on Return On Equity, leverage, liquidity and the companies total asset turnover. The Corporate Governance is not influence of the Z-Score, the results indicate that the presence of good corporate governance can increase the value of the company by itself and to avoid the potential for bankruptcy. The increasing of good corporate governance, the company's potential bankruptcy can be avoided Keywords : Good Corporate Governance, Financial Performance, z score